1995
DOI: 10.1080/00268979500101621
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption-desorption kinetics in nanoscopically confined oligomer films under shear

Abstract: The method of molecular dynamics computer simulations is employed to study oligomer melts confined in ultra-thin films and subjected to shear. The focus is on the self-diffusion of oligomers near attractive surfaces and on their desorption, together with the effects of increasing energy of adsorption and shear. It is found that the mobility of the oligomers near an attractive surface is strongly decreased. Moreover, although shearing the system forces the chains to stretch parallel to the surfaces and thus inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 30 publications
2
47
0
Order By: Relevance
“…In these more recent studies, it was found that the effective diffusion coefficient depends markedly on the surfactant used, for the same polymer and annealing temperature. Because the surfactant can only affect the polymer motion inside the galleries, one concludes that this motion of the intercalated polymer is the process which dictates the intercalation kinetics [33]. Furthermore, for some systems the intercalating polymers were found to possess a mobility that was much faster than the self-diffusion coefficient of the corresponding polymer in the bulk [31], or in a thin film [34].…”
Section: Kinetics Of Polymer Melt Intercalationmentioning
confidence: 98%
“…In these more recent studies, it was found that the effective diffusion coefficient depends markedly on the surfactant used, for the same polymer and annealing temperature. Because the surfactant can only affect the polymer motion inside the galleries, one concludes that this motion of the intercalated polymer is the process which dictates the intercalation kinetics [33]. Furthermore, for some systems the intercalating polymers were found to possess a mobility that was much faster than the self-diffusion coefficient of the corresponding polymer in the bulk [31], or in a thin film [34].…”
Section: Kinetics Of Polymer Melt Intercalationmentioning
confidence: 98%
“…Moreover, they exhibit shear thinning for very moderate shear rates and the onset of this non-Newtonian behaviour shifts to lower shear rates in narrower confinements [6], [7]. Molecular-Dynamics (MD) computer simulations have proven to be effective in interpreting this counter-intuitive behaviour of nanoscopically confined films [11]- [15] and unvealed the origin of the "glassy" dynamics in ultra-thin confinements [11], [12].…”
mentioning
confidence: 99%
“…Our previous studies [12]- [14] revealed a strong tendency of the adsorbed chains to align and stretch against the confining surface for the shear rates employed. This behaviour clearly is a major contribution to the shear thinning observed [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 In addition, molecular dynamics simulations of oligomers in confined geometries under shear also show enhanced desorption/adsorption kinetics from attractive surfaces. 25,26 The large shear stresses at the silicon surface can account for the enhanced desorption/adsorption kinetics, but several details of the observed enhancement in the kinetics are not fully resolvable. For example, the enhanced desorption/adsorption kinetics do not clearly indicate that wall slip is occurring in this system.…”
mentioning
confidence: 99%